Technology-Based Risk Management: Risk Management Innovation in the Era of Fintech and Open Banking - Hendra, Joni; Ummah, Resta Sofiatul; Saputri, Nurul Wulandari; Iklima, Cahaya; Marchella, Violla (CV. Rayyan Dwi Bharata, 2025)
The digital transformation of the banking industry has fostered the emergence of various financial innovations, including fintech and open banking, significantly reshaping the landscape of risk management. This study aims to analyze how financial institutions adopt technology-based risk management systems to address the complexity and rapid changes in the digital era. Using a qualitative descriptive approach, this research explores the implementation of technologies such as big data analytics, artificial intelligence (AI), and blockchain in detecting, analyzing, and mitigating risks arising from the integration of banking services with third-party platforms. The findings reveal that the adoption of digital technologies not only enhances risk management efficiency but also expands the capacity for real-time and predictive risk detection. Nonetheless, challenges such as cyber risk, dependency on digital infrastructure, and the need for adaptive regulation remain critical concerns. This study is expected to contribute to the development of responsive and sustainable risk management strategies in the era of fintech and open banking.